2017
DOI: 10.1007/s11010-017-3021-1
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic insight of platelet apoptosis leading to non-surgical bleeding among heart failure patients supported by continuous-flow left ventricular assist devices

Abstract: Non-surgical bleeding (NSB) is the most common clinical complication in heart failure (HF) patients supported by continuous-flow left ventricular assist devices (CF-LVADs). In this study, oxidative stress and alteration of signal pathways leading to platelet apoptosis were investigated. Thirty-one HF patients supported by CF-LVADs were divided into bleeder (n=12) and non-bleeder (n=19) groups. Multiple blood samples were collected at pre-implant (baseline) and weekly up to one-month post-implant. A single bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Furthermore, a high rate of platelet damage and dysfunction has been observed in patients supported with an LVAD . Steinlechner et al ., and more recently Baghei et al ., reported that platelet aggregation is significantly reduced in the majority of patients after LVAD implantation .…”
Section: Acquired Coagulopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a high rate of platelet damage and dysfunction has been observed in patients supported with an LVAD . Steinlechner et al ., and more recently Baghei et al ., reported that platelet aggregation is significantly reduced in the majority of patients after LVAD implantation .…”
Section: Acquired Coagulopathiesmentioning
confidence: 99%
“…Finally, in a recent publication, Mondal et al . investigated a potential mechanism of platelet apoptosis in CF‐LVAD patients who developed bleedings within 1 month post‐implantation . Higher platelet reactive oxygen (ROS) generation, a decrease in total antioxidant capacity and elevated oxidized low‐density lipoproteins were observed in the bleeding group, suggesting that the body's antioxidant capacity may not have been sufficient to combat the deleterious effects of ROS in patients who experienced a bleeding event .…”
Section: Acquired Coagulopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus has been on platelet activation and platelet MPs but these have so far not shown a utility as predictors of adverse events or stratifiers. However, there are other platelet parameters, all measurable by flow cytometry, that have potential as patient risk stratifiers, or even predictors, for bleeding complications in patients with CF-VADs [18][19][20]. These include significantly greater levels of reactive oxygen species, mitochondrial damage, surface phosphatidylserine (PS) expression/apoptosis, and significantly decreased expression of α2bβ3 on the platelet surface, in bleeders compared to non-bleeders [18][19][20].…”
Section: Plateletsmentioning
confidence: 99%
“…91,92 VADs may also be associated with changes in intracellular reactive oxygen species (ROS) in platelets and mitochondrial damage that could potentially contribute to increased nonsurgical bleeding observed in these patients. 93,94 Ligand binding to GPIb-IX-V or GPVI leads to rapid elevation of intracellular ROS, through a direct interaction of cytoplasmic sequences of GPIb and GPVI with the adaptor protein, tumor necrosis factor receptor associated factor 4 (TRAF4), which links these receptors to p47 phox of the NADPH oxidase (Nox) enzyme complex that generates ROS which is important for the propagation of Syk-dependent signals downstream of GPVI and GPIb. 95,96 Conclusions and Future Implications…”
Section: Platelets and Inflammationmentioning
confidence: 99%